The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5152/balkanmedj.2014.9535
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception Outcomes after Cochlear Implantation in Children with GJB2/DFNB1 associated Deafness

Abstract: Author contributions: Concept -M.D-C., E.S-S.; Supervision -I.F.; Materials -M.D-C., E.S.S., V.L., V.I.; Data Collection&/or Processing -B.Z., V.I.; Analysis&/or Interpretation -M.D-C., E.S-S., V.I.; Literature Search -M.D-C., E.S-S., V.L., V.I.; Writing -M.D-C., E.S-S., V.I.; Critical Reviews -I.F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Besides, the SIR score improved to 4 which meant that his pronunciation was clearly enough that could be understood by an acquaintance. However, the speech recognition scores with CI on both ears were lower than previously reported patients who have normal cochlea [ 31 , 32 ]. It has been reported that the outcomes of cochlear implantation in patients with IP-III malformation were generally poorer than patients with normal cochlea [ 22 , 27 , 33 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Besides, the SIR score improved to 4 which meant that his pronunciation was clearly enough that could be understood by an acquaintance. However, the speech recognition scores with CI on both ears were lower than previously reported patients who have normal cochlea [ 31 , 32 ]. It has been reported that the outcomes of cochlear implantation in patients with IP-III malformation were generally poorer than patients with normal cochlea [ 22 , 27 , 33 ].…”
Section: Discussioncontrasting
confidence: 68%
“…The discrepancies among these studies may be because different tests were administered to evaluate patients with different lengths of CI use ( Table 1 ). Some studies only addressed the outcomes for the first 2 years after implantation [ 11 , 12 , 15 , 20 , 22 ], while others preformed assessments until postoperative year 3 [ 13 , 14 , 18 , 19 ]. None of these studies, however, has reported long-term follow-up results in patients with different types of genetic deafness.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports on the post-CI speech outcomes in patients with GJB2 mutations are controversial. Davcheva-Chakar, et al [ 14 ], reported results from 2 years’ follow-up after CI in children with GJB2 -related deafness and a control group of children with deafness of unknown etiology. Both groups showed similar improvements in speech perception scores after CI.…”
Section: Introductionmentioning
confidence: 99%